Albumin Biomimetic Nanocorona Improves Tumor Targeting and Penetration for Synergistic Therapy of Metastatic Breast Cancer. (30th January 2017) - Cao, Haiqiang; Zou, Lili; He, Bin; Zeng, Lijuan; Huang, Yongzhuo; Yu, Haijun; Zhang, Pengcheng; Yin, Qi; Zhang, Zhiwen; Li, Yaping
Abstract : The synergistic combination of photothermal and RNA interference therapy demonstrates great potential for effective treatment of metastatic breast cancer, but their efficacy is limited by the poor delivery efficiency to tumor. Herein, it is reported that an albumin biomimetic nanocorona (DRI‐S@HSA) can accomplish the high accumulation and deep penetration within tumor tissues, thereby holding great promise for synergistic therapy. DRI‐S@HSA is prepared by camouflaging human serum albumin (HSA) onto an IR‐780 and small interfering RNA‐loaded cell‐penetrating peptide nanoassembly (DRI‐S). In metastatic 4T1 breast cancer cells, DRI‐S@HSA can be largely internalized, and cause significant inhibition on cell migration and proliferation in combination with laser irradiation. Surprisingly, in vivo, the albumin camouflage in DRI‐S@HSA produces a 2.5‐fold enhancement on tumor accumulation compared to the undecorated DRI‐S, and dramatically improves the deep penetration capacity in tumor mass. Moreover, a single DRI‐S@HSA treatment plus 808 nm laser irradiation results in an 83.6% inhibition on tumor growth and efficient prevention of lung metastases. Taken together, the findings can provide an encouraging biomimetic tumor‐targeted drug delivery strategy to inhibit tumor progression and prevent lung metastases of breast cancer. Abstract : The targeted drug delivery of nanomedicine to tumor remains a great challenge for combinational therapy of metastatic breast cancer. Herein, an albumin biomimetic nanocorona (DRI‐S@HSA) loading photothermal agent IR‐780 and Twist small interfering RNA can accomplish high accumulation and deep penetration within tumor tissues, thereby holding great promise for synergistic therapy of tumor progression and metastasis of breast cancer.